Berberine Extends Lifespan in C. elegans Through Multi-Target Synergistic Antioxidant Effects - Yingshuo Bei; Ting Wang; Shuwen Guan (Antioxidants)
Aging is a process of gradual functional decline in complex physiological systems and is closely related to the occurrence of various diseases. Berberine, a bioactive alkaloid derived from Coptis chinensis (Huanglian), has emerged as a promising candidate for anti-aging interventions. This study comprehensively investigated the lifespan-extending effects and molecular mechanisms of berberine in C. elegans through integrated approaches including lifespan assays, locomotor activity analysis, oxidative stress challenges, and transcriptomic profiling. Furthermore, genetic models of mutant and transgenic worms were employed to delineate their interactions with the insulin/IGF-1 signaling (IIS) pathway. Our results demonstrate that berberine extended the mean lifespan of wild-type worms by 27%. By activating transcription factors such as DAF-16/FOXO, HSF-1, and SKN-1/NRF2, berberine upregulated antioxidant enzyme expression, reduced lipofuscin accumulation, and improved stress resistance. Transcriptomic analysis revealed significant changes in lipid metabolism-related genes, particularly in pathways involving fatty acid synthesis, degradation, and sphingolipid metabolism. These findings establish that berberine exerts multi-target anti-aging effects through coordinated activation of stress-responsive pathways and metabolic optimization, providing mechanistic insights for developing natural product-based geroprotective strategies.